Advances in anaerobic membrane bioreactor technology for municipal wastewater treatment: A 2020 updated review. (September 2020) - Vinardell, S.; Astals, S.; Peces, M.; Cardete, M.A.; Fernández, I.; Mata-Alvarez, J.; Dosta, J.
Abstract: The application of anaerobic membrane bioreactors (AnMBR) for mainstream municipal sewage treatment is almost ready for full-scale implementation. However, some challenges still need to be addressed to make AnMBR technically and economically feasible. This article presents an updated review of five challenges that currently hinder the implementation of AnMBR technology for mainstream sewage treatment: (i) membrane fouling, (ii) process configuration, (iii) process temperature, (iv) sewage sulphate concentration, and (v) sewage low organics concentration. The gel layer appears to be the main responsible for membrane fouling and flux decline being molecules size and morphology critical properties for its formation. The review also discusses the advantages and disadvantages of five novel AnMBR configurations aiming to optimise fouling control. These include the integration of membrane technology with CSTR or upflow digesters, and the utilisation of scouring particles. Psychrophilic temperatures and high sulphate concentrations are two other limiting factors due to their impact on methane yields and membrane performance. Besides the methane dissolved in the effluent and the competition for organic matter between sulphate reducing bacteria and methanogens, the review examines the impact of temperature on microbial kinetics and community, and their combined effect on AnMBR performance. Finally, the review evaluates the possibility to pre-concentrate municipal sewage by forward osmosis. Sewage pre-concentration is an opportunity to reduce the volumetric flow rate and the dissolved methane losses. Overall, the resolution of these challenges requires a compromise solution considering membrane filtration, anaerobic digestion performance and economic feasibility. Highlights: Five main challenges were identified for mainstream AnMBR implementation. Membrane fouling appears influenced by molecules size and morphology. New AnMBR configurations are gaining attention to improve fouling control. Psychrophilic temperatures and influent sulphate are limiting factors for AnMBRs. Sewage pre-concentration could improve the applicability of AnMBR technology.